Region Coloring in Minahasa Regency Using Sequential Color Algorithm - Yevie Ingamita; Nelson Nainggolan; Benny Pinontoan (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2019)
Graph Theory is one of the mathematical sciences whose application is very wide in human life. One of theory graph application is Map Coloring. This research discusses how to color the map of Minahasa Regency by using the minimum color that possible. The algorithm used to determine the minimum color in coloring the region of Minahasa Regency that is Sequential Color Algorithm. The Sequential Color Algorithm is an algorithm used in coloring a graph with k-color, where k is a positive integer. Based on the results of this research was found that the Sequential Color Algorithm can be used to color the map of Minahasa Regency with the minimum number of colors or chromatic number Ï‡(G) obtained in the coloring of 25 sub-districts on the map of Minahasa Regency are 3 colors (Ï‡(G) = 3).